Pragmatic Analysis on Social Media (Instagram) - Dina Hanifa; Sennya Nurditasari; Muhammad Natsir (RIRAI Publisher, 2021)
This research was aimed to analyze the pragmatic on Social Media. The analysis was focused on the application of cooperative principles. This research was conducted by using qualitative method. The data of this study were the Netizen comments on the influencer account. The account of the influencer was Anyageraldine. The data source is taken from instagram where nowdays many people use instagram for doing communication and interaction. The writers observed and choosed the data. There were some techniques of data analysis performed, namely: determining, observing, choosing, analyzing, and drawing conclusion. Based on the data analysis conducted, it was found that the cooperative principle at 2012 – 2016 are Maxim of Quantity is 4, Maxim of Quality is 2, Maxim of Relevance is 2, and Maxim of Manner is 7. And the writers also found the Cooperative Principles at 2017 – 2020 are Maxim of Quantity is 1, Maxim of Quality is 5, Maxim of Relevance is 7 and Maxim of Manner is 2. This is influenced by the influencer’s (Anya Geraldine) behaviour as we know that our behaviour make the people statements or comments, it means our behaviour also decided what the Cooperative Principles that the people will use.